Association of systemic lupus erythematosus clinical features with European population genetic substructure. - Elisa Alonso-Perez (Public Library of Science (PLoS), 2011)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease with a very varied spectrum of clinical manifestations that could be partly determined by genetic factors. We aimed to determine the relationship between prevalence of 11 clinical features and age of disease onset with European population genetic substructure. Data from 1413 patients of European ancestry recruited in nine countries was tested for association with genotypes of top ancestry informative markers. This analysis was done with logistic regression between phenotypes and genotypes or principal components extracted from them. We used a genetic additive model and adjusted for gender and disease duration. Three clinical features showed association with ancestry informative markers: autoantibody production defined as immunologic disorder (P = 6.8×10(-4)), oral ulcers (P = 6.9×10(-4)) and photosensitivity (P = 0.002). Immunologic disorder was associated with genotypes more common in Southern European ancestries, whereas the opposite trend was observed for photosensitivity. Oral ulcers were specifically more common in patients of Spanish and Portuguese self-reported ancestry. These results should be taken into account in future research and suggest new hypotheses and possible underlying mechanisms to be investigated. A first hypothesis linking photosensitivity with variation in skin pigmentation is suggested.